2010 International Conference on Information and Communication Technology Convergence (ICTC) 2010
DOI: 10.1109/ictc.2010.5674258
|View full text |Cite
|
Sign up to set email alerts
|

Throughput, delay and bandwidth efficiency of IEEE 802.15.4a using CSS PHY

Abstract: The IEEE 802.15.4 standard is a short range wireless technology. As a revision to this standard, IEEE 802.15.4a introduces new options for PHY (physical layer) to enable ranging. In this paper, we investigate the theoretical maximum throughput and minimum delay of the un-slotted version of 802.15.4a using CSS (Chirp Spread Spectrum) PHY. The throughput and delay limits are derived for different frequency bands and data rates along with the formulae. Moreover, we calculate the bandwidth efficiency for both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Analytical results consider (24). Without retransmissions, the obtained results are very similar to the ones obtained in [28, 29], which again verify the proposed formulation.…”
Section: Performance Evaluationsupporting
confidence: 83%
See 1 more Smart Citation
“…Analytical results consider (24). Without retransmissions, the obtained results are very similar to the ones obtained in [28, 29], which again verify the proposed formulation.…”
Section: Performance Evaluationsupporting
confidence: 83%
“…By comparing the basic access mode (labelled DATA/ACK in the figure) without retransmissions against the results presented in [29], we conclude that the difference in the results for the minimum average delay, Dmin, is because authors in [29] have not considered the time needed to switch the radio between the different states ( rxSetupTime ), as it has been done in [24].…”
Section: Performance Evaluationmentioning
confidence: 98%
“…By comparing IEEE 802.15.4 in the basic access mode (labeled DATA/ACK in the legend) for the case without retransmissions with the one presented in [15], we conclude that the differences in terms of minimum average delay, D min , are justified by the fact that the authors in [15] have not considered the time needed to switch the radio between the different states (i.e., rxSetupTime) [10].…”
Section: Rxmentioning
confidence: 96%
“…15.4 has been widely accepted as the de facto standard for WSNs, enabling to provide ultralow complexity, cost and power for low-data rate wireless connectivity for wireless sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In [3] the authors have shown that one fundamental reason for IEEE 802.15.4/4a MAC inefficiency is overhead, where the use of ACK control packets can decrease the bandwidth efficiency about 10%.…”
Section: Introductionmentioning
confidence: 99%